Implementation of Project Based Learning Model with Windows Movie Maker Media in Improvement of Short Story Writing - R. Panca Pertiwi Hidayati; Siti Nurjanah (JETL (Journal of Education, Teaching and Learning), 2017)
This research is motivated by the lack of ability of students in writing short stories. This research apply project based learning model with windows movie maker media. The formulation of the problem is "Whether the application of project based learning model with windows movie maker media can improve the ability to write short stories of students." In accordance with the formulation of the problem, the hypothesis of this research is the application of project based learning model with windows movie maker media can improve writing skills Short stories of students greater than or equal to 75. This study is based on the Kemmis and Taggart self-reflection model that lasts for 2 cycles. Based on the observer's observation, teacher activity in learning has increased at every meeting and cycle, starting from cycle I teachers get the average value of 82,5. In the second cycle get an average value of 97.5. Similarly, student activity on cycles 1 obtained an average of 75, and in the last 2 cycles the average score was 95. The results of the questionnaire generally showed that students responded positively to the short story writing model using project based learning and media windows movie maker . Implementation of Project Based Learning model with Windows Movie Maker Media can improve students' writing skill. It is shown by the average value of pretes of 42.4 increased in cycle I with an average of 78, then increased again in cycle II with an average of 85.4. Hypothesis test results in this study obtained t count equal to 6.992. Meanwhile, with the degree of freedom 19 at the level of significance 0.05 (5%) obtained t table value of 1.729. So t count> t table is 6.992> 1.729 so H0.